Managing : toward accountability for performance - Albanese, Robert (Homewood, Ill. : R.D. Irwin ; Georgetown, Ont. : Irwin-Dorsey, 1981)
A student-oriented introduction to the academic disciple of management. It surveys a wide range of topics relevant to effective managing.
Includes bibliographical references and indexes.
oif 19/03/15
Loan
Keywords: Management; Organization; Personnel management